In vitro study of ATP1A3 p.Ala275Pro mutant causing alternating hemiplegia of childhood and rapid-onset dystonia-parkinsonism - Ruan, Dan-dan; Zou, Jing; Liao, Li-sheng; Ji, Ming-dong; Wang, Ruo-li; Zhang, Jian-hui; Zhang, Li; Gao, Mei-zhu; Chen, Qian; Yu, Hong-ping; Wei, Wen; Li, Yun-fei; et al. (Frontiers in Neuroscience, 2024)
Introduction We previously reported that ATP1A3 c.823G>C (p.Ala275Pro) mutant causes varying phenotypes of alternative hemiplegia of childhood and rapid-onset dystonia-parkinsonism in the same family. This study aims to investigate the function of ATP1A3 c.823G>C (p.Ala275Pro) mutant at the cellular and zebrafish models. Methods ATP1A3 wild-type and mutant Hela cell lines were constructed, and ATP1A3 mRNA expression, ATP1A3 protein expression and localization, and Na+-K+-ATPase activity in each group of cells were detected. Additionally, we also constructed zebrafish models with ATP1A3 wild-type overexpression (WT) and p.Ala275Pro mutant overexpression (MUT). Subsequently, we detected the mRNA expression of dopamine signaling pathway-associated genes, Parkinson’s disease-associated genes, and apoptosisassociated genes in each group of zebrafish, and observed the growth, development, and movement behavior of zebrafish. Results Cells carrying the p.Ala275Pro mutation exhibited lower levels of ATP1A3 mRNA, reduced ATP1A3 protein expression, and decreased Na+-K+-ATPase activity compared to wild-type cells. Immunofluorescence analysis revealed that ATP1A3 was primarily localized in the cytoplasm, but there was no significant difference in ATP1A3 protein localization before and after the mutation. In the zebrafish model, both WT and MUT groups showed lower brain and body length, dopamine neuron fluorescence intensity, escape ability, swimming distance, and average swimming speed compared to the control group. Moreover, overexpression of both wild-type and mutant ATP1A3 led to abnormal mRNA expression of genes associated with the dopamine signaling pathway and Parkinson’s disease in zebrafish, and significantly upregulated transcription levels of bad and caspase-3 in the apoptosis signaling pathway, while reducing the transcriptional level of bcl-2 and the bcl-2/bax ratio. Conclusion This study reveals that the p.Ala275Pro mutant decreases ATP1A3 protein expression and Na+/K+-ATPase activity. Abnormal expression of either wild-type or mutant ATP1A3 genes impairs growth, development, and movement behavior in zebrafish.